2016
DOI: 10.1097/md.0000000000004808
|View full text |Cite
|
Sign up to set email alerts
|

Early risk prognosis of free-flap transplant failure by quantitation of the macrophage colony-stimulating factor in patient plasma using 2-dimensional liquid-chromatography multiple reaction monitoring-mass spectrometry

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Despite differing from rather routinely used two value regimes (below-above cut-offs) for separation of samples/individuals, separation of FGR from CTRL/SGA was successfully employed. Examples of other clinical studies in which it was found that a three value regime was suitable for fulfilling the task to separate two conditions are "early risk prognosis of free-flap transplant failure", "MGMT promoter methylation for selecting glioblastoma patients into trials omitting Temozolomide", and "diagnostic criteria for high-dimensional metabolic data in newborn screening for medium-chain acyl-CoA dehydrogenase deficiency" [22,32,33], but also with sFlt-1/PlGF ratio (<38 and >85) [34,35] and PlGF measurements alone to predict still-birth FGR (<12 and >100) [36]. In agreement with the obtained PCA results, good separation was achieved with the cumulative score discriminator of 1.0 as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite differing from rather routinely used two value regimes (below-above cut-offs) for separation of samples/individuals, separation of FGR from CTRL/SGA was successfully employed. Examples of other clinical studies in which it was found that a three value regime was suitable for fulfilling the task to separate two conditions are "early risk prognosis of free-flap transplant failure", "MGMT promoter methylation for selecting glioblastoma patients into trials omitting Temozolomide", and "diagnostic criteria for high-dimensional metabolic data in newborn screening for medium-chain acyl-CoA dehydrogenase deficiency" [22,32,33], but also with sFlt-1/PlGF ratio (<38 and >85) [34,35] and PlGF measurements alone to predict still-birth FGR (<12 and >100) [36]. In agreement with the obtained PCA results, good separation was achieved with the cumulative score discriminator of 1.0 as well.…”
Section: Discussionmentioning
confidence: 99%
“…To determine "best cut-off" values for quotients A, B, and C (see Raw Data Processing) that can be used to classify an individual spectrum (patient) as either belonging to the FGR I or the CTRL I group, a Youden index analysis was performed [17,22,23]. The first independent measurement series MS1 from both the per protocol set (PPS) for CTRL I (n = 14) and FGR I (n = 14) were chosen as training set "O" (Scheme 1 and Supplemental Scheme S1).…”
Section: Youden Index Analyses For Determining Cut-off Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate the sequential function of endogenous MCSF [51], IL8, and IL6 in wound healing which in case of overexpression may be clinically managed by administering appropriate medication, i.e., management of an individuals' systemic inflammatory status to reduce or even prevent conspicuities and complications during perioperative and postoperative periods. Concomitant medication may become an important if not indispensable part of state-of-the-art flap surgery in the future.…”
Section: Issues In Flap Surgerymentioning
confidence: 99%